Talking Stick Learning Model on Science Learning Outcomes Of Grade V Students - Sitanggang, Widodo; Sirait, Esti Marlina; Sihombing, Lisbet Novianti (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to investigate the effect of the Talking Stick learning model on fifth-grade students’ learning outcomes in Science and Social Studies (IPAS) at SD Negeri 091608 Sinaksak. The background of this research is the low student achievement, as many students failed to reach the Minimum Mastery Criteria (KKTP). The research employed a quantitative approach using a one-group pretest-posttest design. The participants were 25 fifth-grade students. The research instrument consisted of 30 multiple-choice questions administered in both pretest and posttest stages. The findings revealed a significant improvement in students’ achievement, with the mean score rising from 42.4 in the pretest to 88.08 in the posttest. The N-Gain analysis produced a score of 0.7214, categorized as high. These results indicate that the Talking Stick learning model is effective in enhancing students’ understanding of IPAS, particularly on the topic “Parts of the Earth.” Furthermore, this method fosters active participation, builds confidence in expressing opinions, and strengthens collaboration among students. Therefore, the Talking Stick model can serve as an enjoyable and interactive learning strategy that teachers may adopt to improve the quality of IPAS instruction in elementary schools